The formal sector wage premium and firm size - Eliane Badaoui; Eric Strobl; Frank A. Walsh (Institute for the Study of Labor (IZA), 2007)
We show theoretically that when larger firms pay higher wages and are more likely to be caught defaulting on labour taxes, then large high-wage firms will be in the formal sector and small low-wage firms will be in the informal sector. The formal sector wage premium is thus just a firm size wage differential. Using data from the South African labour force survey we illustrate that firm size is indeed the key variable determining whether a formal sector premium exists.
Keywords: 330; Informal sector; wage premium; firm size; Lohnstruktur; Informeller Sektor; Betriebsgröße; Südafrika